Pott's Spine Presenting With Concurrent Paraspinal, Retropharyngeal, and Wrist Abscesses: A Rare Case Report - Bibek Shrestha; Sangam Neupane; Nikhil Ranjan Das; Subodh Acharya; Santosh Khadka; Shrawan Dhungana; Dinesh Kafle (Clinical Case Reports, 2026)
ABSTRACT Spinal tuberculosis may present atypically with multifocal cold abscesses without neurological deficit or constitutional symptoms. Concurrent lumbosacral paraspinal, retropharyngeal, and wrist abscesses, though rare, should raise suspicion for tuberculosis, and early diagnosis with MRI and GeneXpert enables effective minimally invasive management with anti‐tubercular therapy.